Enhancement of adenosine A2A signaling improves dopamine D2 receptor antagonist-induced dyskinesia via β-arrestin signaling - Nagaoka, Koki; Asaoka, Nozomi; Nagayasu, Kazuki; Shirakawa, Hisashi; Kaneko, Shuji (Frontiers in Neuroscience, 2023)
Repeated administration of dopamine D2 receptor (D2R) antagonists, which is the treatment for psychosis, often causes tardive dyskinesia (TD). Despite notable clinical demand, effective treatment for TD has not been established yet. The neural mechanism involving the hyperinhibition of indirect pathway medium spiny neurons (iMSNs) in the striatum is considered one of the main causes of TD. In this study, we focused on adenosine A2A receptors (A2ARs) expressed in iMSNs and investigated whether pharmacological activation of A2ARs improves dyskinetic symptoms in a TD mouse model. A 21-day treatment with haloperidol increased the number of vacuous chewing movements (VCMs) and decreased the number of c-Fos-positive iMSNs in the dorsal striatum. Haloperidol-induced VCMs were reduced by acute intraperitoneal administration of an A2AR agonist, CGS 21680A. Consistently, haloperidol-induced VCMs and decrease in the number of c-Fos-positive iMSNs were also mitigated by intrastriatal injection of CGS 21680A. The effects of intrastriatal CGS 21680A were not observed when it was concomitantly administered with a β-arrestin inhibitor, barbadin. Finally, intrastriatal injection of an arrestin-biased D2R agonist, UNC9994, also inhibited haloperidol-induced VCMs. These results suggest that A2AR agonists mitigate TD symptoms by activating striatal iMSNs via β-arrestin signaling.